Optimal design of viscous damper in buildings - Kiew, Kim Mei. (2011)
This report investigates the relationship of the configuration of viscous dampers and the responses of building under seismic load. A nine-storey building was used in this project and the responses were analyzed using SAP 2000 when it was subjected to earthquake ground motion.In chapter one, the background information which led to the objectives of this study was provided. Then, a brief introduction of the earthquake engineering theory and several means of structural control were presented in chapter two. Subsequently, the methodology of this study, the formulation of the structural model and literature review of previous research works were showed in this chapter. In this project, two different approaches were used for finding out a better way to obtain the optimal solution.